High-quality chromosome-level genome assembly and full-length transcriptome analysis of the pharaoh ant Monomorium pharaonis. Issue 12 (15th December 2020) - Gao, Qionghua; Xiong, Zijun; Larsen, Rasmus Stenbak; Zhou, Long; Zhao, Jie; Ding, Guo; Zhao, Ruoping; Liu, Chengyuan; Ran, Hao; Zhang, Guojie
Abstract: Background: Ants with complex societies have fascinated scientists for centuries. Comparative genomic and transcriptomic analyses across ant species and castes have revealed important insights into the molecular mechanisms underlying ant caste differentiation. However, most current ant genomes and transcriptomes are highly fragmented and incomplete, which hinders our understanding of the molecular basis for complex ant societies. Findings: By hybridizing Illumina, Pacific Biosciences, and Hi-C sequencing technologies, we de novo assembled a chromosome-level genome for Monomorium pharaonis, with a scaffold N50 of 27.2 Mb. Our new assembly provides better resolution for the discovery of genome rearrangement events at the chromosome level. Analysis of full-length isoform sequencing (ISO-seq) suggested that ∼15 Gb of ISO-seq data were sufficient to cover most expressed genes, but the number of transcript isoforms steadily increased with sequencing data coverage. Our high-depth ISO-seq data greatly improved the quality of gene annotation and enabled the accurate detection of alternative splicing isoforms in different castes of M. pharaonis . Comparative transcriptome analysis across castes based on the ISO-seq data revealed an unprecedented number of transcript isoforms, including many caste-specific isoforms. We also identified a number of conserved long non-coding RNAs that evolved specifically in ant lineages and several that were conserved across insect lineages. Conclusions: We produced a high-quality chromosome-level genome for M. pharaonis, which significantly improved previous short-read assemblies. Together with full-length transcriptomes for all castes, we generated a highly accurate annotation for this ant species. These long-read sequencing results provide a useful resource for future functional studies on the genetic mechanisms underlying the evolution of social behaviors and organization in ants.